2021
DOI: 10.1111/medu.14652
|View full text |Cite
|
Sign up to set email alerts
|

Innovating medical education—Bringing the clinical environment online

Abstract: provided only if the student requests them through free-form, usergenerated commands. The system then shows the requested clinical assessment findings as high-definition photos, sounds and/or text.The student determines whether the assessment finding is normal or abnormal and reports it, resembling a CS session. Diverse patient profiles have been included in the tool, such as BIPOC, LGBTQ+ and other marginalised populations, to expose students to a wider range of assessment findings than would typically be ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…3 Several studies have already demonstrated the benefits of VRLEs in comparison with or in addition to traditional teaching modalities in undergraduate medical education. [4][5][6][7] VRLEs are believed to provide a more enhanced learning experience when compared with partially immersive VR technologies. 8 However, they are educational tools and do not by themselves teach.…”
mentioning
confidence: 99%
“…3 Several studies have already demonstrated the benefits of VRLEs in comparison with or in addition to traditional teaching modalities in undergraduate medical education. [4][5][6][7] VRLEs are believed to provide a more enhanced learning experience when compared with partially immersive VR technologies. 8 However, they are educational tools and do not by themselves teach.…”
mentioning
confidence: 99%